Inelastic deformation of metallic glasses under dynamic cyclic loading. (15th March 2021) - Duan, Y.J.; Qiao, J.C.; Wada, T.; Kato, H.; Wang, Y.J.; Pineda, E.; Crespo, D.
Abstract: Dynamic mechanical analysis was performed in two metallic glasses that show markedly distinct β relaxation features. The confined flow defects of free-volume zones and the inelastic deformation behavior result into a significant mechanical hysteresis loop in dynamic cyclic loadings, which is described with a viscoelastic model. Annealing below the glass transition temperature T g decreases the concentration of free-volume zones. The understanding of the inelastic deformation, which is related to free-volume zones, is critical and may provide a new avenue into the mechanical properties' improvement of high entropy metallic glasses. Graphical abstract: Image, graphical abstract